Regulation of N-acetylglutamate synthesis in Salmonella typhimurium. - Abdelal, A T (1979)
N-Acetylglutamate synthase was purified to homogeneity from Salmonella typhimurium. The enzyme is subject to repression and feedback inhibition by arginine. Inhibition studies indicated that arginine exerts its effect primarily by reducing the affinity of the enzyme for glutamate.